ANALISIS KELAYAKAN USAHATANI JAMBU AIR MERAH DELIMA (Syzygium samarangense (Blume) Merr. & Perry.) DI KABUPATEN DEMAK (Studi Kasus di Kelurahan Betokan Kecamatan Demak Kabupaten Demak) - Muhammad Suheli; Dewi Hastuti; Eka Dewi Nurjayanti (Universitas Wahid Hasyim, 2013)
The research objective was to determine why farmers cultivate delima water apple and analyze the costs, revenues, income, level of feasibility in terms of break even point (BEP) and return cost ratio (R/C ratio) on the farm delima water apple in Demak Regency. The methodology used is a case study in the Betokan Village, Demak District, Demak Regency in 2012. Recruitment of respondents was all farmers delima water apple, with has trees over 3 years of age. In this study of 26 respondents Betokan Villages. The data used are primary data and secondary data. The data was collected by interview, observation, quesioner, recording, and literature review. The results showed that the analysis of the total cost value of the land tax is Rp.1.921.206,00/season and land rent of cost Rp.2.796.254,00/season. While revenue is Rp.8.766.015,00/season. Revenue using the cost analysis of land value tax is Rp.6.844.809,00/season, and the use of land rental value of Rp.5.969.761,00/season. BEP value of production quantity is equal to 154,71 Kg/season. While BEP rupiah is Rp.1.261.206,64/season. The R/C ratio in the delima water apple farming the land tax value of the analysis is as large as 4,56, while the R/C ratio using land rental value is as large as 3,13. Results of the analysis using the above qualifications break even point (BEP) and return cost ratio (R/C ratio). Keywords: Cost, delima water apple, feasibility analysis, income, revenue.